2010
DOI: 10.1037/a0020644
|View full text |Cite
|
Sign up to set email alerts
|

Self-discrepancy: Comparisons of the psychometric properties of three instruments.

Abstract: In 2 studies, the psychometric properties of 3 methods for measuring real-ideal and real-ought self-discrepancies were compared: the idiographic Self-Concept Questionnaire-Personal Constructs, the nonidiographic Self-Concept Questionnaire-Conventional Constructs, and the content-free Abstract Measures. In the 1st study, 125 students at a university clinic completed the 3 instruments and measures of anxiety and depression before individual therapy. In the 2nd study, 278 undergraduates completed the 3 instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 71 publications
(120 reference statements)
6
41
0
Order By: Relevance
“…Our results show that the "general primary control cultural discrepancy" between the control orientation an individual claims s/he would use in certain situations, and the control orientation s/he thinks should be used in the same situations, is negatively related with well-being for both over and under cultural discrepancy. This corresponds to previous studies suggesting that any discrepancy between what a "person thinks he ought to do" and what "he thinks he will actually do" will be expressed in low well-being ( Festinger, 1957, Higgins, 1987, Rogers, 1951, Sanderson et al, 2008Watson, Bryan & Thrash, 2010). Thus, the expected negative correlation between "general primary control cultural discrepancy" and well-being was confirmed.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our results show that the "general primary control cultural discrepancy" between the control orientation an individual claims s/he would use in certain situations, and the control orientation s/he thinks should be used in the same situations, is negatively related with well-being for both over and under cultural discrepancy. This corresponds to previous studies suggesting that any discrepancy between what a "person thinks he ought to do" and what "he thinks he will actually do" will be expressed in low well-being ( Festinger, 1957, Higgins, 1987, Rogers, 1951, Sanderson et al, 2008Watson, Bryan & Thrash, 2010). Thus, the expected negative correlation between "general primary control cultural discrepancy" and well-being was confirmed.…”
Section: Discussionsupporting
confidence: 65%
“…Internal Cronbach coefficient consistencies was α = 0.60. For the reliability and validity of self-discrepancy measures see: Watson, et al, (2010).…”
Section: Instrumentsmentioning
confidence: 99%
“…While Higgins (1987) reported intercorrelation ranges from .53-.76, more recent studies have reported intercorrelations ranging from .67-.80 (Tangney et al, 2008) to even .92 (Hart et al, 1997). Some have argued that these high intercorrelations suggest that only a single discrepancy is being measured (Gramzow, Sedikides, Panter, & Insko, 2000;Tangney et al, 1998), while others continue to find evidence for two distinct discrepancies (Phillips & Silvia, 2010;Watson et al, 2010). Another plausible explanation for inconsistent results may be related to the limited ability of the utilized instruments to discriminate between anxiety and depression;…”
Section: Empirical Support For Self-discrepancy Theorymentioning
confidence: 99%
“…As individuals internalize the standards and expectations held by society, ethnic or religious groups, and significant others, the infusion of obligations and duties into the perception of one's own goals and desires makes the differentiation of Ideal and Ought selves problematic (Watson et al, 2010). However, the limited ability to separate these constructs may be due to problematic methods and instruments that are designed to identify self-discrepancies.…”
Section: Current Self-discrepancy Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation